Narasi sejarah yang tidak setara: mengurangi bias gender dalam buku teks sejarah Indonesia - Utama, Taqwa Ridlo (Jurnal Pendidikan Sejarah Indonesia, 2024)
Gender bias in Indonesian history education remains a significant issue that requires attention. This research aims to reduce such disparities by exploring the often-overlooked representation of women's roles. Using a descriptive qualitative method and a literature review approach, this study analyzes the historiography dominated by patriarchal perspectives in 10th-grade high school history textbooks, specifically on the topic of the Islamic kingdoms in Indonesia. By applying feminist pedagogy, the research highlights issues of gender inequality in historical narratives. The analysis is conducted within the framework of cultural feminism, exploring Indonesian values and culture to enrich women's narratives. Prominent female figures in leadership, military, politics, law, and economics are highlighted to create a more inclusive narrative. The findings of this study are expected to contribute to the development of gender-sensitive teaching materials that align with a more flexible and contextual curriculum paradigm.